2015
DOI: 10.1021/om500984y
|View full text |Cite
|
Sign up to set email alerts
|

Rh–POP Pincer Xantphos Complexes for C–S and C–H Activation. Implications for Carbothiolation Catalysis

Abstract: The neutral Rh­(I)–Xantphos complex [Rh­(κ3-P,O,P-Xantphos)­Cl] n , 4, and cationic Rh­(III) [Rh­(κ3-P,O,P-Xantphos)­(H)2]­[BArF 4], 2a, and [Rh­(κ3-P,O,P-Xantphos-3,5-C6H3(CF3)2)­(H)2]­[BArF 4], 2b, are described [ArF = 3,5-(CF3)2C6H3; Xantphos = 4,5-bis­(diphenylphosphino)-9,9-dimethylxanthene; Xantphos-3,5-C6H3(CF3)2 = 9,9-dimethylxanthene-4,5-bis­(bis­(3,5-bis­(trifluoromethyl)­phenyl)­phosphine]. A solid-state structure of 2b isolated from C6H5Cl solution shows a κ1-chlorobenzene adduct, [Rh­(κ3-P,O,P-Xan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 66 publications
5
40
0
Order By: Relevance
“…21 Similarly to chloride, the oxygen atom of the mer-coordinate diphosphine of the latter has tendency to be displaced by the hydride ion. The addition of KH to 7 in tetrahydrofuran leads to the anionic pentahydride [OsH 5 {xant(P i Pr 2 ) 2 }] - (8), containing a κ 2 -P,P-bidentate diphosphine. In the presence of the crown ether 18-crown-6, yellow crystals of the [K (18-crown-6)] + -salt were obtained in 66% yield.…”
Section: Scheme 1 Formation Of H 2 By Sequential Addition Of H + Andmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Similarly to chloride, the oxygen atom of the mer-coordinate diphosphine of the latter has tendency to be displaced by the hydride ion. The addition of KH to 7 in tetrahydrofuran leads to the anionic pentahydride [OsH 5 {xant(P i Pr 2 ) 2 }] - (8), containing a κ 2 -P,P-bidentate diphosphine. In the presence of the crown ether 18-crown-6, yellow crystals of the [K (18-crown-6)] + -salt were obtained in 66% yield.…”
Section: Scheme 1 Formation Of H 2 By Sequential Addition Of H + Andmentioning
confidence: 99%
“…Weller and co-workers have demonstrated that 4,5-bis(diphenylphosphino)-9,9dimethylxanthene (xantphos) has the ability of changing its coordination fashion in several relevant rhodium-and iridium-mediated processes, 6 such as the hydroacylation 7 and carbothiolation 8 of alkenes and alkynes and the dehydrocoupling of amineboranes. 9 Transition metal polyhydrides are compounds having enough hydrogen atoms bonded to the metal center of a L n M fragment to form at least two different types of ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the cationic part in 6 exhibits a slightly distorted square‐pyramidal coordination geometry at the rhodium atom with the λ 4 ‐trifluorosulfanyl ligand located in a trans position to the ether function of the phosphine with O1−Rh1−S1a and O1−Rh1−S1b angles of 169.78(17)° and 170.6(2)°, respectively. The Rh−S bond lengths (Rh1−S1a 2.195(9) Å, Rh1−S1b 2.164(11) Å) are significantly smaller when compared to the one in [Rh(SH)( t Bu xanPOP)] (Rh−S 2.2865(4) Å or in various cationic xantphos‐type Rh (III) −S complexes as for instance [Rh(xanPOP)(C 6 H 4 COMe)(SMe)][BAr F 4 ] (Rh−S 2.3373(14) Å, xanPOP=4,5‐bis(diphenylphosphino)‐9,9‐dimethylxanthene, Ar F =3,5‐(CF 3 ) 2 C 6 H 3 ) [8,11] . The SF 3 ligand displays an Rh⋅⋅⋅F interaction of 2.418(3) Å, which results in a small F1−S1a−Rh angle of 72.3(3)° as well as the significantly elongated bond between the sulfur atom and the fluorine atom F1 of 1.880(7) Å.…”
Section: Resultsmentioning
confidence: 99%
“…First, methylcobalt(I) I should be generated from Co(acac) 2 , Xantphos, and AlMe 3 [ 28 29 ]. Oxidative addition of the allylic C(sp 3 )–H bond to I would proceed to afford η 3 -allylcobalt(III) intermediate II , which is tautomerized to η 1 -allylcobalt(III) III by the assistance of the oxygen atom in the Xantphos ligand [ 30 ]. When using α-olefin as a substrate, the cobalt atom should be located at the terminal position due to the avoidance of steric repulsion between the bulky Xantphos ligand and an alkyl substitution (similar to the case of nucleophilic η 1 -allylpalladium species [ 31 – 39 ]), whereas the cobalt atom preferred to reside at the internal position when allylarenes and 1,4-dienes were employed in our previous studies [ 28 29 ].…”
Section: Resultsmentioning
confidence: 99%